Severe head injury in children: emergency access to neurosurgery in the United Kingdom. Issue 7 (22nd June 2006) - Tasker, R C; Morris, K P; Forsyth, R J; Hawley, C A; Parslow, R C
Abstract : Objective: To determine the scale of acute neurosurgery for severe traumatic brain injury (TBI) in childhood, and whether surgical evacuation for haematoma is achieved within four hours of presentation to an emergency department. Methods: A 12 month audit of emergency access to all specialist neurosurgical and intensive care services in the UK. Severe TBI in a child was defined as that necessitating admission to intensive care. Results: Of 448 children with severe head injuries, 91 (20.3%) underwent emergency neurosurgery, and 37% of these surgical patients had at least one non-reactive and dilated pupil. An acute subdural or epidural haematoma was present in 143/448 (31.9%) children, of whom 66 (46.2%) underwent surgery. Children needing surgical evacuation of haematoma were at a median distance of 29 km (interquartile range (IQR) 11.8–45.7) from their neurosurgical centre. One in four children took longer than one hour to reach hospital after injury. Once in an accident and emergency department, 41% took longer than fours hours to arrive at the regional centre. The median interval between time of accident and arrival at the surgical centre was 4.5 hours (IQR 2.23–7.73), and 79% of inter-hospital transfers were undertaken by the referring hospital rather than the regional centre. In cases where the regional centre undertook the transfer, none were completed within four hours of presentation—the median interval was 6.3 hours (IQR 5.1–8.12). Conclusions: The system of care for severely head injured children in the UK does not achieve surgical evacuation of a significant haematoma within four hours. The recommendation to use specialist regional paediatric transfer teams delays rather than expedites the emergency service.